Subcutaneous Fat Triacylglycerols Profile from Iberian Pigs as a Tool To Differentiate between Intensive and Extensive Fattening Systems - Gallardo, Emerenciana; Narváez-Rivas, Monica; Pablos, Fernando; Jurado, J. Marcos; León-Camacho, Manuel (Journal of Agricultural and Food Chemistry, 2012)
Triacylglycerols of subcutaneous fat of Iberian pigs reared on two different feeding systems, extensive and intensive, have been determined by gas chromatography with a flame ionization detector. Analyses were performed on a column coated with a bonded stationary phase (50% phenyl?50% methylpolysiloxane) with hydrogen as the carrier gas. Lipids were extracted by melting the subcutaneous fat in a microwave oven and then filtering and dissolving in hexane. A total amount of 1995 samples from several campaigns were considered. Palmitoyl-stearyl-oleoyl glycerol and palmitoyl-dioleoyl glycerol were the most abundant triacylglycerols found in the samples. A study on the discriminating power of the triacylglycerols to differentiate samples according to the pig feeding system was performed. By using the triacylglycerols as chemical descriptors, principal component analysis, linear discriminant analysis, and soft independent modeling of class analogy were applied. Dioleoyl-linoleoyl glycerol and oleoyl-dilinoleoyl glycerol were the most discriminating variables. Variable?variable plots of these two glycerols allow separation of the samples according to their content.
doi: 10.1021/jf2045312doi: 10.1021/jf2045312The following values have no corresponding Zotero field: publisher: American Chemical Society
Keywords: gas chromatography; iberian pig; pattern recognition; subcutaneous fat; triacylglycerols